2022
DOI: 10.3389/fonc.2022.878529
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of EXOC1, BCL2, CCAT2, and CARD8 Genes and Susceptibility to Cervical Cancer in the Northern Chinese Han Population

Abstract: Cervical cancer (CC) is one of the main malignant tumors that threaten the health and lives of women around the world, and its morbidity and mortality rate ranks fourth. At present, most studies on the genetic background of CC focus on genetic polymorphisms. Single nucleotide polymorphisms (SNPs) are considered clinically as potential diagnostic and therapeutic biomarkers for a variety of tumors. Therefore, we aimed to explore the association between SNPs in different genes (EXOC1 gene, BCL2 gene, CCAT2 gene a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…EXOC1 is the gene exocyst complex component 1 and is involved in cell migration, similar to Sections 5 and 8 [ 42 ]. No literature was found that supports the connection between EXOC1 and CC; however, genetic mutations in EXOC1 have been associated with breast and cervical cancer [ 46 , 47 ]. Combining our experimental data and the literature evidence, EXOC1 may be inferred as a dark biomarker of mCC due to its involvement in cell migration processes, and transcriptomics may not be the ideal technology to investigate its functional roles.…”
Section: Resultsmentioning
confidence: 99%
“…EXOC1 is the gene exocyst complex component 1 and is involved in cell migration, similar to Sections 5 and 8 [ 42 ]. No literature was found that supports the connection between EXOC1 and CC; however, genetic mutations in EXOC1 have been associated with breast and cervical cancer [ 46 , 47 ]. Combining our experimental data and the literature evidence, EXOC1 may be inferred as a dark biomarker of mCC due to its involvement in cell migration processes, and transcriptomics may not be the ideal technology to investigate its functional roles.…”
Section: Resultsmentioning
confidence: 99%